The influence of various physico-chemical process parameters on kinetics and growth mechanism of struvite crystallisation - Ariyanto, Eko; Sen, Tushar; Ang, Ha Ming (Elsevier, 2014)
In response to struvite formation problems in wastewater treatment plants (WWTP), this mechanistic growth kinetic study of struvite crystal (MgNH4PO4.6H2O) was undertaken to determine the cause of preferential accumulation and to provide the remediation information to the designer of WWTP. Struvite is the mineral phase of one of the urinary tract stones of human and animals also. Here the authors presented the struvite crystal growth formation kinetics mechanism under different physico-chemical process parameters such as supersaturation (Mg2+, NH4+, PO34-), solution pH, stirrer speed, temperature, impurities and seeding conductions. To measure the growth rate of struvite crystals and to identify its various dependence system parameters, laboratory measurements were conducted in an isothermal batch 1 l stirred seeded crystalliser. Supersaturation and pH have been found to be the most influential parameters for struvite crystallisation.It was found that growth rate increased with an increase in solution pH in the pH range of 8–9. The rate of change of ortho-phosphate concentration in the bulk solution increases with increasing supersaturation ratio. The growth rate increased with increase in temperature. Higher NaCl salt concentration and higher speed also produced higher struvite growth kinetics. Fundamentally struvite crystal formation followed a classical diffusion–reaction mass transfer mechanism and overall mass transfer coefficients (KL) under various physico-chemical process parameters have been determined. The kinetic rate constants were also calculated by fitting a first-order kinetic model and power law model to the experimental data obtained. It was also found that there was increase in product crystal size with increase in solution pH, stirrer speed and amount of salts due to slow nucleation followed by fast growth process. Struvite crystallisation may also have implication in an alternative sustainable and economical recovery of phosphorous from concentrated waste water stream.